2011
DOI: 10.1007/s00228-011-1022-7
|View full text |Cite
|
Sign up to set email alerts
|

Flupirtine is a safe alternative drug in patients with hypersensitivity to NSAIDs

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…In the absence of high quality, controlled studies on the abuse liability associated with FLP that is suggested from single cases and its GABAergic mechanism of action, we sought to provide first naturalistic data from a large German pharmacovigilance database. Considering that FLP is widely used in clinical practice for the treatment of various pain syndromes and still subject of ongoing research, there is a particular need for an adequate post‐authorization safety surveillance.…”
Section: Discussionsupporting
confidence: 82%
“…In the absence of high quality, controlled studies on the abuse liability associated with FLP that is suggested from single cases and its GABAergic mechanism of action, we sought to provide first naturalistic data from a large German pharmacovigilance database. Considering that FLP is widely used in clinical practice for the treatment of various pain syndromes and still subject of ongoing research, there is a particular need for an adequate post‐authorization safety surveillance.…”
Section: Discussionsupporting
confidence: 82%
“…Flupirtine has been used as a prescription analgesic in Germany and some other countries for about 30 years, where it has generally been considered to be a safe drug with a low potential for liver enzyme elevations [3, 6, 7], as also reflected in the German prescribing information [8]. Flupirtine was even recommended as a safe alternative for patients experiencing AEs during treatment with nonsteroidal anti‐inflammatory drugs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Flupirtine has been used as a prescription analgesic in Germany and some other countries for about 30 years, where it has generally been considered to be a safe drug with a low potential for liver enzyme elevations [3, 6, 7], as also reflected in the German prescribing information [8]. Flupirtine was even recommended as a safe alternative for patients experiencing AEs during treatment with nonsteroidal anti‐inflammatory drugs [6]. In limited studies with tinnitus patients (24 patients treated with 2 × 100 mg/day for 3 weeks [4]) or Creutzfeldt‐Jakob disease patients (13 patients treated with 3–4 × 100 mg/day for up to 10 months [10]), elevated liver enzymes were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…constipation). Normally, it is well tolerated and a safe alternative in patients with hypersensitivity to NSAIDs [12]. The spectrum of side effects includes a very rare, mild and transient elevation of liver enzymes, aggravation of preexisting liver disease and, in single cases, severe and fatal liver failure [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%